A mente na perspectiva do pragmatismo linguístico: o erro categorial de Renè Descartes e a pragmática de Gilbert Ryle - Oliveira, Victória Karoline Ramos de (2019)
The problem of the mind-body relationship, as presented by the Cartesian tradition, is considered, from the advent of the linguistic turn, a philosophical pseudoproblem originated by the misuse of language. It is with this perspective that in 1949 Gilbert Ryle inaugurates the contemporary philosophy of mind, claiming that the root of this pseudoproblem was a categorical error of the Official Doctrine, reaffirmed by Descartes and perpetuated by our expressions of everyday use about the mental. Ryle's proposal includes that the descriptions of philosophical behaviorism are a decisive alternative to Cartesian dualism. This proposal, however, did not resist the development of the philosophy of mind, and was overshadowed by the excitement of new scientific discoveries and naturalism. However, as it is intended to show, the same has not happened with all their criticisms or with their reasoning, that is, that the problem is a problem that persists as a problem of language use. Such a problem, as discussed here, can be glimpsed from the pragmatic perspective of the notion of employment, when the various forms of employing the same concept, both in the philosophy of mind and in the sciences, give rise to varied attributions of meanings. These variations, in themselves, deserve our attention because they pose the problem in the perspective of linguistic pragmatism, as well as open up new philosophical questions